Does politics matter? Explaining swings in wind power installations - Espen Moe (AIMS Energy, 2017)
This is a social science article on the politics of wind power, and on whether or not politics actually matters. While it may seem obvious that politics actually does, I argue that the arguments that we encounter about wind power very often are about economics, technology or geography, arguments that have something deterministic to them, and which leaves politics a lesser factor. Against this, I argue that while these arguments may go a long way toward explaining the general upward trajectory of wind power, they do a bad job of explaining swings in wind power installations, why some countries are more successful at wind power in general, and why within countries, you typically have periods of both stops and starts. For this, we need a political explanation. Of these, there are many, but from the vantage point of political economy, I suggest a focus on vested interests, among other reasons because this is an explanation that can be used to analyze both democracies and non-democracies, and both presidential and parliamentarian systems. Methodologically, the study is a qualitative comparative case-study of five countries (US, Denmark, Japan, Germany, China) employing a combination of John Stuart Mill’s comparative methods and process-tracing. The main finding is that if you want to explain swings in wind power installations, you need to focus on the political system, and in particular on the interest politics that goes on behind the scenes. While economic, technological, or geographic explanations all provide useful amounts of understanding, neither explanation can explain swings. There is only one explanation that remains constant and important in every one of the five cases. Economics, technology and geography play different roles in different contexts to different extents. Politics on the other hand always plays a role.